How Do Undergraduate Biology Instructors Engage With the Open Educational Resource Life Cycle? - Senn, Lillian G.; Heim, Ashley B.; Vinson, Erin; Smith, Michelle K. (Frontiers in Education, 2022)
Open Educational Resources (OER) are widely used instructional materials that are freely available and promote equitable access. OER research at the undergraduate level largely focuses on measuring student experiences with using the low cost resources, and instructor awareness of resources and perceived barriers to use. Little is known about how instructors work with materials based on their unique teaching context. To explore how instructors engage with OER, we surveyed CourseSource users, an open-access, peer-reviewed journal that publishes lessons primarily for undergraduate life sciences courses. We asked questions aligned with the OER life cycle, which is a framework that includes the phases: Search, Evaluation, Adaptation, Use, and Share. The results show that OER users come from a variety of institution types and positions, generally have positions that focus more on teaching than research, and use scientific teaching practices. To determine how instructors engage throughout the OER life cycle, we examined the frequency of survey responses. Notable trends include that instructors search and evaluate OER based on alignment to course needs, quality of the materials, and ease of implementation. In addition, instructors frequently modify the published materials for their classroom context and use them in a variety of course environments. The results of this work can help developers design current and future OER repositories to better coincide with undergraduate instructor needs and aid content producers in creating materials that encourage implementation by their colleagues.